Estimation of the parameters of the Caddy reciprocal M-at-age model for the construction of natural mortality vectors - Abella A.; Serena F.; Caddy J.F. (Dynamique des populations marines, 1998)
In Mediterranean demersal trawl fisheries, recruitment for most species to the gear starts in their first year of life. This is mainly due to the utilization of cod end stretched mesh sizes of 40 mm or lower. Although comparable data are not available for the Mediterranean, in a study on natural mortality rate at age for a variety of invertebrates and fish world-wide, Caddy (1991) showed that a simple reciprocal relationship reasonably describes the decline in natural mortality with age to the adult value of M used in assessments of mature fish. As many Mediterranean demersal species recruit to the ground in the first year of life, it would be misleading to model yield due to fishing assuming constant death rates throughout life. The consequences of this assumption are explored for Mediterranean hake by Abella et al. (in press.) by means of yield per recruit calculations assuming rapid declines in M with age in the first few years of life to a relatively low constant mortality, and declining availability to trawls of the few individuals surviving to maturity. Even if no direct estimates of M-at-age exist for Mediterranean demersal fish, all vectors generated were similar to M-at-age estimates for related North Sea demersal fish as determined from MSVPA.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)